Patient with heart failure: importance to treat valvular diseases. (23rd December 2020) - Adamo, Marianna; Alos, Benjamin; Metra, Marco; Lefèvre, Thierry; Swaans, Martins J; Gheorghe, Livia; Tschöpe, Carsten; Krackhardt, Florian; Alfieri, Ottavio; Bouleti, Claire
Abstract: COVID-19 pandemic is causing an unprecedented burden on healthcare resources and this includes treatment of heart failure and valvular heart diseases (VHD). Percutaneous procedures have broadened the number of patients with VHD who could be treated. However, COVID-19 pandemic has challenged their implementation. The risk of in-hospital infection, resources reallocation, reduced access to hospital caused a substantial delay of VHD treatment with an increased risk of clinical worsening and mortality. Now, the pandemic is not ended and subsequent waves are likely. Reorganization of our healthcare resources is needed, including a proper algorithm for patients' prioritization, based on the severity of their valve disease, their life expectancy, complexity of the intervention, and the resources available. A wider use of telemedicine for patients' selection and follow-up and any measurement that can shorten the duration of the hospital stay must be adopted. Patients' and healthcare staff screening for COVID-19 and all needed procedures to prevent infection will continue to be mandatory. Percutaneous procedures, compared to surgery, are associated with a lower risk of infection and a lower need for in-hospital resources, including a shorter duration of hospital stay. This may favour their adoption when the risk of viral infection is high.